Motivation Among Student In Islamic Elementary School Pada Pengembangan Media Audio Visual - Aulia Tri Oktaviani; Fika Amelia; Isti Safitri Khasanah; Muhammad Ibnu Haekal; Wismanto Wismanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In the modern era of education, the focus of learning has shifted from teacher orientation to student orientation. As educators, it is important to design learning methods that are in accordance with technological developments. Today, learning that is too teacher-centered and theoretical tends to reduce student interest. Therefore, the use of audio-visual media such as learning videos can increase student engagement, provide deep meaning, and arouse high enthusiasm for learning. This study aims to 1) explain the level of student enthusiasm when using audio-visual learning media, and 2) evaluate the impact and interest of students on audio-visual based learning media in the learning process. This research was conducted at Madrasah Ibtidaiyah Ibn Aqil Pekanbaru. This research is a descriptive qualitative research that uses data collection methods in the form of direct observation, interviews, and literature studies. Research findings show that lecture-dominated learning tends to make learners lose interest and focus on themselves. The results of the study showed that 1) when students were introduced to the use of audio-visual media such as learning videos, most of them felt very enthusiastic and excited in following the learning process, while only one student showed less interest. 2) Thus, it can be concluded that the use of audio-visual learning media can increase student enthusiasm at the elementary school level.